A Study of Panel Data Approach: Analysis of Minimum Wage and Poverty In Yogyakarta, Indonesia - Nashiruddin, Rafie; Yuniarti, Dini; Saleh, Rahmat (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
In this study, the main focus is to see the relationship between the minimum wage and poverty in the Special Region of Yogyakarta. By adding independent variables, namely average years of schooling, economic growth, and open unemployment rate. The data used in this study is secondary data from the official website of the Yogyakarta Central Bureau of Statistics (BPS) from 5 districts / cities with a time span of 2013 to 2023. Data analysis in this study uses panel data analysis that combines time series and cross section data with a fixed effect model (FEM) approach processed with Stata14 static tools. The results showed that the minimum wage (LUMK) had a negative and significant effect on poverty (LPM) and the open unemployment rate (TPT) had a significant positive effect on poverty (LPM), while the average years of schooling (RRLS) and economic growth (PE) had no effect on poverty. However, simultaneously all independent variables have a significant effect on poverty in the Special Region of Yogyakarta.